Realising the potential of urine and saliva as diagnostic tools in sport and exercise medicine - Lindsay, A.; Costello, J. T. (Sports Medicine, 2017)
Accurate monitoring of homeostatic perturbations following various psychophysiological stressors is essential in sports and exercise medicine. Various biomarkers are routinely used as monitoring tools in both clinical and elite sport settings. Blood collection and muscle biopsies, both invasive in nature, are considered the gold standard for the analysis of these biomarkers in exercise science. Exploring non-invasive methods of collecting and analysing biomarkers that are capable of providing accurate information regarding exercise-induced physiological and psychological stress is of obvious practical importance. This review describes the potential benefits, and the limitations, of using saliva and urine to ascertain biomarkers capable of identifying important stressors that are routinely encountered before, during, or after intense or unaccustomed exercise, competition, over-training, and inappropriate recovery. In particular, we focus on urinary and saliva biomarkers that have previously been used to monitor muscle damage, inflammation, cardiovascular stress, oxidative stress, hydration status, and brain distress. Evidence is provided from a range of empirical studies suggesting that urine and saliva are both capable of identifying various stressors. Although additional research regarding the efficacy of using urine and/or saliva to indicate the severity of exercise-induced psychophysiological stress is required, it is likely that these non-invasive biomarkers will represent "the future" in sports and exercise medicine.